Advances in intestinal flora for the development, diagnosis and treatment of CRC - Hu, Ruiyao; Qiu, Yuting; Liu, Dong-ang; Chen, Shiyu; Chen, Keyi; Xu, Yue; Yuan, Jinghua; Zhang, Xinling; Li, Xiaoping (Frontiers in Microbiology, 2025)
Colorectal cancer (CRC), being prevalent among digestive tract malignancies, exhibits substantial mortality and morbidity rates. The intestinal microbiota, predominantly located in the colorectum, is diverse and comprises both conditionally pathogenic bacteria that can promote CRC development and probiotics that can inhibit it to some extent. Intestinal flora is associated with colorectal cancer, affecting its onset and progression through metabolites, immune regulation, and damage to the intestinal mucosal barrier. The intestinal flora exhibits significant potential in the diagnosis and treatment of CRC. Certain bacterial species can serve as biomarkers for CRC, aiding in the detection of precancerous and early-stage lesions. For instance, alterations in the abundance of Fusobacterium nucleatum (Fn) and Enterotoxigenic Bacteroides fragilis (ETBF) may indicate an elevated risk of CRC. On the other hand, probiotics such as Bifidobacteria could modulate chemotherapy and immunotherapy, improving treatment outcomes and reducing side effects, making them an effective approach to prevent CRC etiology and act as an adjuvant therapy. This paper focuses on a review of the relationship between intestinal flora and CRC, sorting out its potential role in developing, diagnosing, and treating CRC. It will advance precise, intelligent, and individualised prevention and treatment for CRC.